2003
DOI: 10.1186/cc2416
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Italian version of the Intensive Care Unit Memory tool in the clinical setting

Abstract: IntroductionPatients' memories of intensive care have been investigated in patients admitted to general [1][2][3][4] and medical [5] intensive care units (ICUs), especially in relation to artificial ventilation [1,6] and sedation [7][8][9]. However, the way in which the various studies investigated recollections was not consistent, making comparisons difficult and unclear or even impossible. Therefore, a new and specific instrument with which to assess patients' memories of their ICU stay (ICU Memory [ICUM] to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…Almost two-thirds of patients in the current study had at least one delusional memory, higher than has been reported in many studies 1,3 but comparable to that found by Jones et al (63 versus 76%). 2 More patients in this study recalled seeing strange things (70 versus 51%) while fewer recalled having bad dreams (54 versus 63%) than previously reported.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Almost two-thirds of patients in the current study had at least one delusional memory, higher than has been reported in many studies 1,3 but comparable to that found by Jones et al (63 versus 76%). 2 More patients in this study recalled seeing strange things (70 versus 51%) while fewer recalled having bad dreams (54 versus 63%) than previously reported.…”
Section: Discussionsupporting
confidence: 83%
“…The vivid detail of delusional memories has also been reported elsewhere 2 and may account for the persistence of delusional memories over time. 1-2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion of patients who were not admitted to ICU after surgery despite an admission planned at the time of the anaesthetic visit, allowed a homogeneous sample of patients with the same factors possibly influencing patient memory to be evaluated. In fact, the administration of analgesic and sedatives, which is a common ICU practice, has been demonstrated to influence patient memory of the ICU stay [ 36 , 37 ]. This practice may also influence the memory of the period preceding ICU admission, so we preferred to study the patients exposed to the same risk factors, that is those really admitted to ICU.…”
Section: Discussionmentioning
confidence: 99%
“…The ICU memory tool has been used in previous studies to measure various aspects of memory after intensive care and it has been primarily tested and validated on ICU patients in England and Italy [ 16 - 19 ]. It consists of items about memory on admission to hospital and memory for the ICU stay.…”
Section: Methodsmentioning
confidence: 99%